Cerebral vein thrombosis in patients with Philadelphia‐negative myeloproliferative neoplasms An European Leukemia Net study. Issue 11 (31st July 2014) - Martinelli, Ida; De Stefano, Valerio; Carobbio, Alessandra; Randi, Maria L.; Santarossa, Claudia; Rambaldi, Alessandro; Finazzi, Maria C.; Cervantes, Francisco; Arellano‐Rodrigo, Eduardo; Rupoli, Serena; Canafoglia, Lucia; Tieghi, Alessia; et al.
<x xml:space="preserve">Abstract</x> To investigate the characteristics and clinical course of cerebral vein thrombosis (CVT) in patients with myeloproliferative neoplasms (MPN) we compared 48 patients with MPN and CVT (group MPN‐CVT) to 87 with MPN and other venous thrombosis (group MPN‐VT) and 178 with MPN and no thrombosis (group MPN‐NoT) matched by sex, age at diagnosis of MPN (±5 years) and type of MPN. The study population was identified among 5, 500 patients with MPN, from January 1982 to June 2013. Thrombophilia abnormalities were significantly more prevalent in the MPN‐CVT and MPN‐VT than in MPN‐NoT group (P = 0.015), as well as the JAK2 V617F mutation in patients with essential thrombocythemia (P = 0.059). Compared to MPN‐VT, MPN‐CVT patients had a higher rate of recurrent thrombosis (42% vs. 25%, P = 0.049) despite a shorter median follow‐up period (6.1 vs. 10.3 years, P = 0.019), a higher long‐term antithrombotic (94% vs. 84%, P = 0.099) and a similar cytoreductive treatment (79% vs. 70%, P = 0.311). The incidence of recurrent thrombosis was double in MPN‐CVT than in MPN‐VT group (8.8% and 4.2% patient‐years, P = 0.022), and CVT and unprovoked event were the only predictive variables in a multivariate model including also sex, blood count, thrombophilia, cytoreductive, and antithrombotic treatment (HR 1.97, 95%CI 1.05–3.72 and 2.09, 1.09–4.00, respectively). Am. J. Hematol. 89:E200–E205, 2014. © 2014 Wiley Periodicals, Inc.